Konstruksi Posesif Bahasa Inggris dalam Cerita Pendek There Will Come Soft Rains - Usmala Dewi Siregar; Mulyadi Mulyadi (CaLLs: Journal of Culture, Arts, Literature, and Linguistics)
This study aims to describe the type of possessive construction and the possessive relationship between possessor/PR and possessum/PM in the possessive construction of English in short story There Will Come Soft Rains by Ray Bradbury. The data were taken from sentences contained possessive construction in short story it. The data were collected by reading and noting and were analyzed by means of the distributional method to determine the type of possessive construction relationship and the correspondence method to determine the possessive relationships between the possessor and the possessed. The findings are as follows first, the type of possessive construction was found in short story it was attributive possession. Second, The relationships can be categorized into three possessive relationships, namely the ownership, part-whole, and abstract.